Application of real-time quantitative RT-PCR for improving the diagnosis, treatment, and control of bovine Anaplasmosis - Reinbold, James Brandon (Kansas State University, 2009)
The Office International des Epizooties (OIE) Animal Health Code categorizes bovine anaplasmosis as a notifiable disease. Many species of the genus Anaplasma cause anaplasmosis. Co-infections with two or more Anaplasma spp. occur in cattle. A competitive ELISA is regarded as a reliable test for identifying A. marginale-infected cattle. However, cross-reactivity among related Anaplasma spp. has been reported when using cELISA. In the absence of effective treatment strategies and vaccine availability, anaplasmosis control strategies are primarily focused on disease identification and prevention and development of chemosterilization strategies. Four studies were completed to improve the diagnosis, treatment, and control of bovine anaplasmosis. In the first study, a real-time qRT-PCR was developed to detect as few as 100 copies of 16S rRNA of both A. marginale and A. phagocytophilum in the same reaction. This detection limit was equitable to the minimum infective unit of one A. marginale bacterium. In the second study, qRT-PCR results determined needle-free injection was superior to needle injection for controlling iatrogenic transmission of A. marginale in cattle. The qRT-PCR demonstrated 100% sensitivity by 21 days post-infection and 21 days prior to 100% sensitivity with cELISA. The third study determined the pharmacokinetic parameters of chlortetracycline in group fed, ruminating Holstein steers: volume of distribution (40.9 L⁄kg); rate constant (0.0478 h-1); dose-normalized area under the curve (0.29 h•µg⁄L); clearance (1.8 L⁄kg⁄h); elimination half-life (16.2 h); maximum concentration/dose (4.5 ng⁄mL); and time of maximum concentration (23.3 h). Dose linearity was confirmed for oral chlortetracycline dosages of 4.4, 11, and 22 mg/kg/day. The final study established an in vivo pharmacokinetic-pharmacodynamic relationship between chlortetracycline and anaplasmosis carrier clearance in bovine plasma (85.3 ng/mL). The qRT-PCR confirmed chemosterilization of all oral chlortetracycline-treated cattle within 49 days of treatment. Furthermore, qRT-PCR was an effective alternative to the subinoculation of splenectomized cattle for accurate and precise disease classification. The diagnosis, treatment, and control of anaplasmosis were enhanced through the application of qRT-PCR. Further studies are necessary for determining the mechanism of action between chlortetracycline binding to the 30S ribosome of A. marginale and carrier clearance.
Keywords: Anaplasmosis; PCR; Pharmacokinetics; chlortetracycline; Bovine; chemosterilization; Biology, Microbiology (0410)